GUDA PRAYOGA IN CHAKRADATTA - Remya R. Nath; Veena G. Rao (International Journal of Applied Ayurved Research, 2016)
Chakradatta, also known as Chikitsasangraha is written by Chakrapani Dutta belonged to the Eastern part of India in the 11th century. The legacy of therapeutic principles specific for the disease recommended by Chakradatta has continued even today among the practitioners. Numbers of single drug remedies are documented in this book. In almost all the chapters Acharya quoted a combination of jaggery. Among them many are still in practice. Here an attempt has been made to analyse the Gudaprayoga in Chakradatta. Jaggery forms the backbone of Asavas and Arishtas. It is good substitute for sugar. Not only that, it comes with a bunch of its own unique health benefits. Jaggery is extensively used in many Indian cuisines also. Need Of The Study: To add additional information about guda prayoga in Ayurvedic medical practice.